2021
DOI: 10.1155/2021/1082963
|View full text |Cite
|
Sign up to set email alerts
|

Development and Parametric Analysis of Vibration System Controlled by Hydraulic Shock Rotary Vibrator

Abstract: The improvement of the energy utilization rate of a hydraulic vibration-excitation system is critical to the research and development of hydraulic vibration equipment. In this paper, a hydraulic vibration-excitation system controlled by a new type of shock rotary vibrator is proposed. A system model considering the pipeline effect was established for the hydraulic shock phenomenon. In addition, the model was compared with the one that does not consider the pipeline effect. The effectiveness of the proposed mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Wang et al 27 29 designed electro-hydraulic exciter consisting of four-way rotary valve and miniature double-acting hydraulic cylinder, described the theoretical formulas for the flow area of various valve port shapes, simulated and analyzed the output vibration characteristics of the electro-hydraulic exciter, and experimentally verified the results. Ren et al 30 proposed a hydraulic vibration excitation system controlled by a novel of shock rotary vibrator, established a system model considering pipeline effect and compared it with the model without considering pipeline effect, and experimentally verified the validity of the proposed model. Liu et al 31 , 32 summarized the research progress of wave generating devices with wave structural impact experiment, pointed out the technical bottlenecks of existing wave generating devices in amplitude preservation and waveform control, and designed push plate type wave generating device based on rotary valve control, realizing a new utilization of electro-hydraulic wave excitation energy.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 27 29 designed electro-hydraulic exciter consisting of four-way rotary valve and miniature double-acting hydraulic cylinder, described the theoretical formulas for the flow area of various valve port shapes, simulated and analyzed the output vibration characteristics of the electro-hydraulic exciter, and experimentally verified the results. Ren et al 30 proposed a hydraulic vibration excitation system controlled by a novel of shock rotary vibrator, established a system model considering pipeline effect and compared it with the model without considering pipeline effect, and experimentally verified the validity of the proposed model. Liu et al 31 , 32 summarized the research progress of wave generating devices with wave structural impact experiment, pointed out the technical bottlenecks of existing wave generating devices in amplitude preservation and waveform control, and designed push plate type wave generating device based on rotary valve control, realizing a new utilization of electro-hydraulic wave excitation energy.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, experimental findings indicated that the vibration waveform harmonic distortion of rotary valve exciter is less than 1% compared with the sine wave. Ren et al [19] proposed rotary valve controlled electro-hydraulic vibration exciter with hollow shaft, investigated the influence of multiple parameters on the exciter vibration characteristics while taking the water hammer effect into account through model simulation and experimental tests, and pointed out that the hydraulic shock induced by the valve controlled flow excitation can improve the exciter vibration characteristics. Liu et al [20] proposed a novel type of wave generating device with rotary valve controlled electro-hydraulic exciter and established mathematical model of wave generating device.…”
Section: Introductionmentioning
confidence: 99%
“…In solved examples, they showed that when the cracks are sufficiently far, their effects on the transmission error are clearly distinguishable, and their lengths can be observed precisely. Gritli et al [17] diagnosed the faults resulting from tooth root cracks in a gear pair. Finite element analysis and dynamic simulations of the gear system performed in MATLAB software can obtain the mesh stiffness of a gear pair.…”
Section: Introductionmentioning
confidence: 99%